Direct vs preimplantation balloon valvuloplasty in transcatheter aortic valve replacement—Systematic review and meta‐analysis of randomized controlled trials and prospective‐matched cohorts. Issue 7 (17th May 2020) - Pranata, Raymond; Vania, Rachel; Alkatiri, Amir Aziz; Firman, Doni
Abstract: Background: This systematic review and meta‐analysis aimed to evaluate the efficacy and safety of direct vs preimplantation balloon valvuloplasty (predilatation) before transcatheter aortic valve replacement (TAVR). Methods: We performed a systematic literature search up until March 2020 from PubMed, SCOPUS, EuropePMC, Cochrane Central Database, ProQuest, and ClinicalTrials.gov . We included randomized controlled trial (RCT) and prospective‐matched cohorts that compared direct TAVR and preimplantation balloon valvuloplasty before TAVR. The primary outcome was the device success as defined by Valve Academic Research Consortium 2. The secondary outcome was a patient‐prosthesis mismatch, the need for balloon postdilatation, composite adverse events, and 1‐year mortality. Results: There were a total of 3078‬ patients from eight studies. This meta‐analysis showed that direct TAVR has a similar device success rate ( P  = .63), the need for postdilatation ( P  = .82), and composite adverse events ( P  = .98) compared with preimplantation balloon valvuloplasty. Subgroup analysis for balloon‐expandable valves showed lower need for balloon postdilatation (risk ratio [RR], 0.63 [0.47, 0.84]; P  = .002; I 2, 0%) in direct TAVR group but higher incidence of acute kidney injury (RR, 3.23 [1.25, 8.40]; P  = .02; I 2, 0%) and major/life‐threatening bleeding (RR, 1.54 [1.17, 2.02]; P  = .002; I 2, 0%). Subgroup analysis for the RCTs alone and RCTs + propensity‐matched cohorts showed similar device success and composite adverse events in both groups. However, pooled RCTs showed a higher need for balloon postdilatation in direct TAVR (RR, 1.83 [1.03, 3.24]; P  = .04; I 2, 0%). Conclusion: Direct TAVR has similar efficacy and safety to preimplantation balloon valvuloplasty. However, better‐designed RCTs are required before drawing a definite conclusion.